Integrated functional and bioinformatics approach for the identification and experimental verification of RNA signals: application to HIV-1 INS - Wolff, Horst (Oxford University Press, 2003)
Regulation of gene expression involves sequence elements in nucleic acids. In promoters, multiple sequence elements cooperate as functional modules, which in combination determine overall promoter activity. We previously developed computational tools based on this hierarchical structure for in silico promoter analysis. Here we address the functional organization of post-transcriptional control elements, using the HIV-1 genome as a model. Numerous mutagenesis studies demonstrate that expression of HIV structural proteins is restricted by inhibitory sequences (INS) in HIV mRNAs in the absence of the HIV-1 Rev protein. However, previous attempts to detect conserved sequence patterns of HIV-1 INS have failed. We defined four distinct sequence patterns for inhibitory motifs (weight matrices), which identified 22 out of the 25 known INS as well as several new candidate INS regions contained in numerous HIV-1 strains. The conservation of INS motifs within the HIV genome was not due to overall sequence conservation. The functionality of two candidate INS regions was analyzed with a new assay that measures the effect of non-coding mRNA sequences on production of red fluorescent reporter protein. Both new INS regions showed inhibitory activity in sense but not in antisense orientation. Inhibitory activity increased by combining both INS regions in the same mRNA. Inhibitory activity of known and new INS regions was overcome by co-expression of the HIV-1 Rev protein.